Amyotrophic lateral sclerosis mortality rates among ethnic groups in a predominant admixed population in Latin America: a population-based study in Ecuador. Issue 5 (3rd July 2019) - Luna, Jaime; Preux, Pierre-Marie; Logroscino, Giancarlo; Erazo, Daniells; Del Brutto, Oscar H.; Boumediene, Farid; Couratier, Philippe; Marin, Benoit
Abstract: Current evidence suggests heterogeneity of amyotrophic lateral sclerosis (ALS) among geographic areas and populations. Lower mortality rates have been reported in admixed populations compared to European origin populations. We aimed to describe and compare ALS mortality rates among ethnic groups using a population-based approach in a multiethnic country. Annual mortality cause registers were searched to determine ALS deaths from the National Institute of Statistics and Censuses in Ecuador (INEC) from 1990 to 2016. Mid-year population was considered for each year. The time trend was assessed using a negative binomial regression. Rate ratio statistics were performed to compare the age and sex standardized rates based on the 2010 US population among ethnic groups. Overall, 570 ALS deaths were identified. ALS mortality showed an age-related profile with a peak between 55 and 70 years. After age–sex standardization on the 2010 US population, mortality rate was 0.33 (CI 0.30–0.36) per 100, 000. The time trend showed an increase of ALS mortality ( p  < 0.001). There was no statistical difference in age–sex standardized mortality rates per 100, 000 when admixed was compared to white ( p  = 0.231) and black ( p  = 0.125). Differences reached statistical significance between admixed and other ethnics ( p  = 0.015). Our population-based study supports the hypothesis that ALS occurrence is lower in predominant admixed populations from Latin America compared to European and Northern American populations. Further studies are needed to clarify the role of ancestral origin in ALS susceptibility.